PROFIT ANALYSIS OF WHOLESALERS AND RETAILERS OFSESAME IN NASARAWA STATE, NIGERIA (FULafia Journal of Science and Technology, 2023)
Profit analysis of wholesalers and retailers of sesame was addressed in the study
Keywords: Wholesalers; retailers; sesame; profit; marketing margin; marketing cost